The relationship between parent child relationship and online grooming risk among early adolescents in Agam Regency - Sarah Ainil Putri; Fauziah Taslim (Talenta Publisher, 2026)
This study aims to examine the relationship between the parent-child relationship and online grooming risk in early adolescents in Agam Regency. The increase in internet use among adolescents is followed by an increased risk of online crime, including online grooming, which the victim is often unaware of. Early adolescents are highly vulnerable due to their need for social affiliation and their limited ability to recognize the risks of online interactions. This study uses a quantitative, correlational design. The study participants were 180 adolescents aged 13-17 years, selected using incidental sampling. Data were collected using the Inventory of Parent and Peer Attachment (IPPA) and the Online Grooming Risk Scale (OGR-S). Data analysis uses Pearson product-moment correlation. Results showed a significant negative relationship between parent-child relationship and online grooming risk (r = -0.735). These findings show that the parent-child relationship has the potential to be a protective factor in reducing the risk of online grooming in early adolescents.